Peran Mahasiswa Dalam Melatih Kreativitas Anak Melalui Lomba Melukis Patung - Qudsiyah, Khikmatul; Prasetyo, Danang; Nusanto, Tri Suyud (Kurnia Mengabdi: Jurnal Pengabdian kepada Masyarakat, 2024)
Students can take part in community service activities (PkM) and assist village communities in developing villages, especially tourist villages, to become a developing tourist attraction and have an impact on the community's economy. On the other hand, tourist villages need to have an academic role involving students in an effort to maximize their tourism potential. Ambarrukmo Yogyakarta College of Tourism annually organizes community service activities coordinated by the Institute for Research and Community Service (LPPM). The purpose of writing this article is to describe the results obtained from carrying out a real work program in Dayakan Hamlet. The activity method used is direct observation in the field and discussion to the target of the individual work program, namely children. And using the mentoring method for the process of implementing the sculpture painting competition at the August 17 competition event. The results obtained are that the community and village managers appreciate and find that the results of student activities are very instrumental in helping the development of Watu Ledhek Tourism Village. The resulting conclusion is that students can play a role in helping the community and village managers develop tourism potential so that it can answer the needs of a tourist village.